Students’ Adaptation Strategies to Parking Space Policies: A Case Study of the Faculty of Performing Arts at ISI Padang Panjang - Qurrata 'Aini, Ratu Sarah; Aziz, Basyarul (Kirana Publisher (KNPub), 2025)
This study discusses the adaptation strategies employed by students of the Faculty of Performing Arts at the Indonesian Institute of the Arts (ISI) Padang Panjang, West Sumatra Province, in response to the campus parking policy. The aim of this research is to explore how students adapt to the parking regulations and to examine both the positive and negative impacts experienced directly by the interviewees on campus. This study uses a qualitative approach with data collection techniques including observation, interviews, and documentation. The results indicate that students have developed various adaptation strategies, such as adjusting their arrival schedules and using alternative routes to campus, including walking. These strategies reflect the students’ efforts to cope with the limitations of parking facilities on campus.